Exonucleolytic proofreading of leading and lagging strand DNA replication errors. - Roberts, J D (1991)
We have asked whether exonucleolytic proofreading occurs during simian virus 40 origin-dependent, bidirectional DNA replication in extracts of human HeLa cells. In addition, we have compared the fidelity of leading and lagging strand DNA synthesis. In a fidelity assay that scores single-base substitution errors that revert a TGA codon in the lacZ alpha gene in an M13mp vector, providing an excess of a single dNTP substrate over the other three dNTP substrates in a replication reaction generates defined, strand-specific errors. Fidelity measurements with two vectors having the origin of replication on opposite sides of the opal codon demonstrate that error rates for two different A.dCTP and T.dGTP mispairs increase when deoxyguanosine monophosphate is added to replication reaction mixtures or when the concentration of deoxynucleoside triphosphates is increased. The data suggest that exonucleolytic proofreading occurs on both strands during bidirectional replication. Measurements using the two simian virus 40 origin-containing vectors suggest that base substitution error rates are similar for replication of the leading and lagging strands.